Drug Discovery And Antiproliferative Effect Of Linear And Circular Aptamers On Colon Cancer (Journal of Pharmaceutical Negative Results, 2023)
The word ‘Sirtuin’ or Sir2 proteins are a class of proteins that possess either mono-ADP-ribosyltransferase, or deacylase activity, including deacetylase. SIRT1 is the most studied mammalian Sirtuins and predominantly localised in the nucleus and cytoplasm. Many Sirtuins targets are involved in cancer and in many types of cancers, SIRT1 is found to be overexpressed. Recent observations support SIRT1 being both an oncogene and a tumour suppressor, depending on the cancer etiology and type of tissue. To answer the question “How can SIRT1 activator (BAS Aptamers) behave as a tumor suppressor in colon cancer?” In this regard, we propose to study the characterisation of the interactions between BAS Aptamers (linear3, linear4, circular3 and circular4) and SIRT1 in human colon cancer cells (HCT116) as the first step towards the development of an alternative chemotherapy for colon cancer diseases. The objectives of current study are to investigate the effects of selected BAS aptamers (Linear3, Linear4, Circular3, and Circular4) on colon cancer cell line. In conclusion, a pharmacological activation of SIRT1 enhanced cell death suggesting a tumour suppressive function of SIRT1 and the high-affinity SIRT1- aptamers identified in this study may be used in the future for cancer treatment.